(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to identify the forms of consumer involvement in the co-creation innovation process, analyze the role of consumers at each stage of design thinking, and examine the benefits and challenges of its implementation in developing user-oriented innovations. The study used the Systematic Literature Review (SLR) method with PRISMA guidelines. Data sources were obtained from Google Scholar, Scopus, ScienceDirect, Springer, and Emerald Publishing with a publication range of 2010–2024. Of the 40 identified articles, 20 were selected based on inclusion and exclusion criteria. Data were analyzed using thematic analysis techniques through a process of selection, extraction, categorization, and synthesis of research findings. The results of the study indicate that co-creation innovation strengthens the effectiveness of design thinking through consumer involvement at the empathize, define, ideate, prototype, and test stages. Consumers act as sources of ideas, development partners, solution testers, and innovation evaluators. This involvement increases the relevance of innovation, consumer engagement, customer loyalty, and the co-learning process. However, its implementation still faces challenges such as variations in consumer participation, multi-stakeholder coordination, resource limitations, and digital technology optimization. These findings underscore the importance of consumer engagement as strategic partners in creating more adaptive and sustainable innovations